(3EOGQI GdLhOI GdTGedI aj GdJYdje GdLGeYjs - (3jhSa MLje(B, (3GdWGFjs; (3GdYHGOj eMeO ahRj(B, s ((3YeGf(B:s (3OGQ GdhQGb ddfTQ hGdJhRjY(B,s, 2007)
(3jVe GdGWGQ GdeYQaj dLhOI GdJYdje , eaGgje eJYdbI HGdLhOI GdTGedI GdJYdjejI , GUdGM GdJYdje GdLGeYj aj Xd GOGQI GdLhOI GdTGedI , GdacQ GdefXhej ddLhO GdTGedI aj GdJYdje GdLGeYj , LhOI GdJYdje GdYGdj , GdGJLGgGJ GdeYGUQI aj GOGQI GdLhOI GdTGedI GdJYdjejI , echfGJ GdLhOI GdTGedI aj GdJYdje , eONd JWHjb fXGe GdLhOI GdTGedI aj GdJYdje GdLGeYj , GdQcGFR GdGSGSjI dJWHjb EOGQI GdLhOI GdTGedI aj GdJYdje GdLGeYj , eMGhQ GdLhOI GdTGedI ef NdGd GdefXhQ GdLGeYj , GOGQI GdLhOLI GdJYdje Yf HYO hGdJYdje GdOLGeYj GdeaJhM , VeGf LhOI GdJYdje GdLGeYj , eJWdHGJ GOGQI GdLhOI GdLGeYjI , GdfeGPL GdeWHbI aj GOGQI GdLhOI GdTGedI GdJYdjejI , GOGQI GdLhOI GdTGedI aj GdJYdje GdLGeYj (B.s
(3HjHdjhZQGajG(B: (3U(B. 423 (3bGFeI GdGTcGd U(B. 15 (3bGFeI GdLOGhd (B17(3U(B.s
Keywords: (3GdEOGQIs; (3GdJYdje GdLGeYjs; (3VHW GdLhOIs